Analysis of Morphometric Variations in the Thickness of the Mandibular Symphysis in Patients at Dr. Mohammad Hoesin General Hospital Palembang, Indonesia - Muzakkie, Mufida; Muhammad Fikri Aulia; S.N.A. Ratna Sari Devi; Ziske Maritska (Sriwijaya Journal of Surgery, 2024)
Introduction. Accurate knowledge of mandibular thickness is necessary for performing surgical treatments on the mandible. The Champy procedure has become the predominant approach for treating fractures of the mandible. Placing plates along these lines is believed to offer the best possible fixing and stability. The objective of this study is to analyze and compare the thickness of the mandible in patients, specifically depending on their gender. The purpose is to gain a more comprehensive understanding of the differences in mandibular architecture across various populations in South Sumatra, Indonesia. Methods. This study is a cross-sectional analytical-observational study. The Department of Radiology of Dr. Mohammad Hoesin Central General Hospital, located in Palembang, conducted the study. We included a total of 103 research participants in this study, all of whom met the specified inclusion criteria. Results. There is a notable difference in the thickness of the lower jawbone in the front part (A and B) that runs parallel to Champy's line, depending on the person's gender. Males have a greater morphometric thickness of the mandibular symphysis in comparison to females. The thickness of the mandibular symphysis closely links to gender disparities. Conclusion. The thickness of symphysis A in men was substantially greater than in females, while the thickness of symphysis B in males was also significantly greater than in females, with a P value less than 0.001.